RETRACTED: Meloidogyne enterolobii risk to agriculture, its present status and future prospective for management - Sikandar, Aatika; Jia, Luming; Wu, Haiyan; Yang, Shanshan (Frontiers in Plant Science, 2023)
Meloidogyne enterolobii, commonly known as guava root-knot nematode, poses risk due to its widespread distribution and extensive host range. This species is recognized as the most virulent root-knot nematode (RKN) species because it can emerge and breed in plants that have resistance to other tropical RKNs. They cause chlorosis, stunting, and yield reductions in host plants by producing many root galls. It is extremely challenging for farmers to diagnose due to the symptoms' resemblance to nutritional inadequacies. This pathogen has recently been considered a significant worldwide threat to agricultural production. It is particularly challenging to diagnose a M. enterolobii due to the similarities between this species and other RKN species. Identified using traditional morphological and molecular techniques, which is a crucial first in integrated management. Chemical control, biological control, the adoption of resistant cultivars, and cultural control have all been developed and effectively utilized to combat root-knot nematodes in the past. The object of this study was to get about the geographical distribution, host plants, symptoms, identification, and control techniques of M. enterolobii and recommend future initiatives to progress its management.